Low emission geothermal power plants with absorption and reinjection of non-condensable gases - Giovanni Manente; Andrea Lazzaretto; Alessio Bardi; Marco Paci; BERTANI, RUGGERO (Universidade do Minho, Departamento de Engenharia Mecânica, Campus Azurém, Guimarães Portugal, 2018)
The gas content in the steam produced by some Italian geothermal fields is far from negligible, being around 5-10%. Several abatement methods are available to reduce the hydrogen sulfide and mercury emissions in dry steam and flash geothermal power plants, most of them relying on the use of chemicals. Recently, the reinjection of H2S in the reservoir was tested in Iceland, a country having limited amounts of non-condensable gases (NCG) in the geothermal reservoirs. The reinjection of NCG in the Italian geothermal fields raises new challenges due to the high content of NCG, especially in the Mt. Amiata area. This paper examines the viability of NCG absorption and reinjection in retrofitting a geothermal plant fed by steam with a high NCG content (8%). The proposed layout includes an absorption column, in place of the AMIS® unit equipping the existing power stations, where H2S and CO2 are absorbed in water at high pressure. From preliminary calculations carried out in Aspen Plus®, it appears that the reinjection of the entire flow of NCG asks for considerable amounts of water and very high pressures (>100 bar). Thus, the study searches for those conditions ensuring an overall H2S abatement similar to that achieved by the plants equipped with the AMIS® unit (>90%), while minimizing the water and power demands. The results show that an overall H2S abatement of 86.4% could be reached using a column pressure of 36 bar and a water supply of 100 ton/hr, and coping with a net power output reduction of 6%. A further increase of H2S abatement in order to match the same performance of the AMIS® plant would lead to more demanding operating conditions in terms of water consumption and power penalty. The 50% abatement of the CO2 in the geothermal fluid is certainly a positive side effect.